Review on program slicing techniques towards program comprehension application / Rozita Kadar, Naemah Abdul Wahab and Jamal Othman - Kadar, Rozita; Abdul Wahab, Naemah; Othman, Jamal (UiTM Cawangan Perlis, 2017)
Presently, the software system has grown in size. One of the main challenges faced by programmers is to keep up with thousand or million lines of source code that needs to be read and understood. The source code is an essential resource for programmers to become familiar with the software system. Program comprehension is important in software engineering activities before performing maintenance tasks. One of the techniques that can assist the programmers in comprehending software system is known as program slicing. Program slicing is the process of extracting parts of source code programs by tracing the programs' control and data flow related to some data item. In this paper, we conduct the literature review on program slicing in order to explore the direction of this method by focusing on various slicing techniques to provide a novel idea in program comprehension application